IMPLEMENTATION OF UNINHABITABLE HOUSE CONSTRUCTION PROGRAM (RUTILAHU) IN CIMANUK VILLAGE, PANDEGLANG REGENCY - Sulaiman, Angga; Yolanda, Elsa (International Peneliti Ekonomi, Sosial dan Teknologi, 2020)
The purpose of regional autonomy is to improve public services and develop democratic life in Indonesia. The form of decentralization of regional autonomy in the hope of being able to provide maximum service to thecommunity. The method used is qualitative research method. The results showed that there are six primary characteristics that determine the Implementation of Uninhabitable Home Improvement Program in Bandung Regency, namely 1) Size and Policy Objectives, 2) resources, 3) Implementors, 4) Organizational Characteristics, 5) Social, Economic, Cultural, and Political Environment, 6) disposition or attitude. Rutilahu improvement program related to stimulant assistance requires involvement and self-help, it is necessary to strengthen the capacity of non-governmental groups (KSM) so that the strategy / implementation of uninhabitable home improvement programs become better in accordance with the expectations and objectives of the Rutilahu program